Comparison of two electronic hand hygiene systems using real-time feedback via wireless technology to improve hand hygiene compliance in an intensive care unit. Issue 1 (25th July 2022) - Generoso, José R.; Casaroto, Eduardo; Neto, Ary Serpa; Prado, Marcelo; Gagliardi, Guilherme M.; de Menezes, Fernando Gatti; Gonçalves, Priscila; Hohmann, Fábio Barlem; Olivato, Guilherme Benfatti; Gonçalves, Gustavo Potratz; Pereira, Andréa Marques; Xavier, Nathalia; et al.
Abstract: Background: Most hand hygiene (HH) intervention studies use a quasi-experimental design, are primarily uncontrolled before-and-after studies, or are controlled before-and-after studies with a nonequivalent control group. Well-funded studies with improved designs and HH interventions are needed. Objectives: To evaluate healthcare worker (HCW) HH compliance with alcohol-based hand rub (ABHR) through direct observation (human observer), 2 electronic technologies, a radio frequency identification (RFID) badge system, and an invasive device sensor. Methods: In our controlled experimental study, 2, 269 observations were made over a 6-month period from July 1 to December 30, 2020, in a 4-bed intensive care unit. We compared HH compliance between a basic feedback loop system with RFID badges and an enhanced feedback loop system that utilized sensors on invasive devices. Results: Real-time feedback by wireless technology connected to a patient's invasive device (enhanced feedback loop) resulted in a significant increase in HH compliance (69.5% in the enhanced group vs 59.1% in the basic group; P = .0001). Conclusion: An enhanced feedback loop system connected to invasive devices, providing real-time alerts to HCWs, is effective in improving HH compliance.